2019
DOI: 10.1007/978-3-030-20351-1_3
|View full text |Cite
|
Sign up to set email alerts
|

Semi-supervised and Task-Driven Data Augmentation

Abstract: Supervised deep learning methods for segmentation require large amounts of labelled training data, without which they are prone to overfitting, not generalizing well to unseen images. In practice, obtaining a large number of annotations from clinical experts is expensive and time-consuming. One way to address scarcity of annotated examples is data augmentation using random spatial and intensity transformations. Recently, it has been proposed to use generative models to synthesize realistic training examples, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
105
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(113 citation statements)
references
References 34 publications
7
105
0
1
Order By: Relevance
“…Although there are works which indicate that such aggressive augmentation may deteriorate the performance of the models in brain-tumor delineation , it is still an open issue. Chaitanya et al (2019) showed that visually nonrealistic synthetic examples can improve the segmentation of cardiac MRI and noted that it is slightly counter-intuitive-it may have occurred due to the inherent structural and deformationrelated characteristics of the cardiovascular system. Finally, elastic transformations often benefit from B-splines (Huang and Cohen, 1996;Gu et al, 2014) or random deformations (Castro et al, 2018).…”
Section: Data Augmentation Using Elastic Image Transformationsmentioning
confidence: 99%
“…Although there are works which indicate that such aggressive augmentation may deteriorate the performance of the models in brain-tumor delineation , it is still an open issue. Chaitanya et al (2019) showed that visually nonrealistic synthetic examples can improve the segmentation of cardiac MRI and noted that it is slightly counter-intuitive-it may have occurred due to the inherent structural and deformationrelated characteristics of the cardiovascular system. Finally, elastic transformations often benefit from B-splines (Huang and Cohen, 1996;Gu et al, 2014) or random deformations (Castro et al, 2018).…”
Section: Data Augmentation Using Elastic Image Transformationsmentioning
confidence: 99%
“…In medical imaging, UDA has been studied in several fields for which multiple diverse datasets are publicly available: brain MRI [20,4], chest X-ray [7], cardiac MRI-CT [13] and others. However, very few studies investigated the use of UDA techniques in knee MRI domain and, more specifically, knee cartilage segmentation.…”
Section: Related Workmentioning
confidence: 99%
“…Comparison between the baseline and the best performing approaches. Here, means and standard deviations of volumetric DSCs are presented for the subject groups of specific KL-grades(1)(2)(3)(4) and for the full test sets. # shows the number of scans in the specific group.…”
mentioning
confidence: 99%
“…Die diesem Konzept zugrundeliegende Idee ist, dass das Aussehen der Objekte in einem Repräsentationsraum weitestgehend kontinuierlich verteilt und die Struktur des Raums durch die initialen Klassen soweit etabliert wird, das neue Klassen eingepasst werden können. Ein anderer Ansatz für das gleiche Problem ist das erlernte Augmentieren von Daten, das heißt, die Generierung von zusätzlichen Trainingsdaten aus wenigen Beobachtungen [5].…”
Section: Transfer Learningunclassified